Evaluation of the antibacterial activity of cashew seed pellicle (Anacardium occidentale L.) (Research, Society and Development, 2022)
Occupying a large part of the Northeast region, the Caatinga biome is composed of a flora rich in several bioactive compounds that are used in the therapeutic industry for the treatment of numerous diseases caused by antibiotic-resistant bacteria, thus justifying the search for new compounds. As an example, we can mention the cashew tree (Anacardium occidentale L.), one of the symbolic plants of the Caatinga. Thus, the objective of the present work was to evaluate the antibacterial activity of cashew nut skin against isolated microorganisms. For this, three different extracts of the cashew kernel skin were used: aqueous, ethanolic and hexane extracts, made in triplicates at concentrations of 0.6 g/mL, 0.8 g/mL, 1.0 g/mL. The microorganisms tested were two Gram-negative strains: Escherichia coli (ATCC 25922) and Serratia marcescens (LEMBiotech Collection) and two Gram-positive strains: Sthapylococcus aureus (ATCC 700698) and Sthapylococcus epidermidis (ATCC 300698). For the extract sensitivity test, the disc diffusion and bacterial inoculum method was employed, in which 10 µL of the test extracts, 10 µL of the antibiotic Amoxillin 50 mg/L, and 10 µL of DMSO were added to each disc. The plates were incubated at 37 ºC for 24h and then the diameters of the concentration halos were measured. It was verified a higher efficiency against Gram-positive strains that presented inhibition halos between 6 mm and 9 mm, varying according to the extract concentration. Furthermore, the best results observed for the extracts affirmed their ability to be employed as an antibacterial.